Embedded Linux projects using Yocto project cookbook : over 70 hands-on recipes for professional embedded Linux developers to optimize and boost their Yocto know-how /: over 70 hands-on recipes for professional embedded Linux developers to optimize and boost their Yocto know-how. (2015) - Gonzalez, Alex
No abstract available